2020
DOI: 10.1002/ejic.202000257
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State Assignments in the Organoplatinum One‐Electron Redox Series [(N^N)PtMes2]n, n = +,0, –,2‐

Abstract: The neutral complexes [(N^N)PtMes 2 ], N^N = bis(1methyl-2-imidazolyl)ketone (bik) or N,N′-disubstituted 1,2-bisiminoacenaphthenes (R-BIAN), Mes = mesityl, were obtained and characterized as Pt II species with planar N 2 PtC 2 configuration and charge transfer transitions in the visible. Reversible one-electron reduction produces radical anion complexes with the spin predominantly localized in the N^N ligand, according

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
2
0
2
Order By: Relevance
“…To confirm the Bian-centered reduction, we performed DFT calculations, which revealed that the lowest unoccupied molecular orbital (LUMO) in complexes 2A – 4A and 2B – 4B was located on the diimine part of Bian ligands (Figure S28). This observation suggests that the electrochemical behavior of novel complexes was based on the π-acceptor character of Bian ligands and the ability of acenaphthene-1,2-diimines to be reduced to acenaphtylene-1,2-diamines. ,, In fact, the ligand-centered reduction is very typical for Bian metal complexes and was previously confirmed by electron paramagnetic resonance spectroscopy. …”
Section: Resultsmentioning
confidence: 59%
“…To confirm the Bian-centered reduction, we performed DFT calculations, which revealed that the lowest unoccupied molecular orbital (LUMO) in complexes 2A – 4A and 2B – 4B was located on the diimine part of Bian ligands (Figure S28). This observation suggests that the electrochemical behavior of novel complexes was based on the π-acceptor character of Bian ligands and the ability of acenaphthene-1,2-diimines to be reduced to acenaphtylene-1,2-diamines. ,, In fact, the ligand-centered reduction is very typical for Bian metal complexes and was previously confirmed by electron paramagnetic resonance spectroscopy. …”
Section: Resultsmentioning
confidence: 59%
“…В литературе представлена методология синтеза ионного триплатинового кластерного комплекса [(Ph 3 C 3 ) 2 Pt 3 (MeCN) 4 ] 2+ (BF 4-) 2 (29) на основе тетрафторбората циклопропения (30) и его аналога с заменой одного из анионов BF 4на Clанион, представляющий собой цепной координационный полимер в кристаллической форме [10]: Нейтральные комплексы [(N^N)PtMes 2 ] (Mes = мезитил), N^N = бис(1-метил-2имидазолил)кетон или N,N'-дизамещенные 1,2-бис-иминоаценафтены были получены и охарактеризованы как производные Pt(II) с планарной конфигурацией N 2 PtC 2 и переходами с переносом заряда в видимой области [15]. Комплексы получены в результате взаимодействия N,N'-хелатных лигандов с цис-[(ДМСО) 2 PtMes 2 ].…”
Section: CLunclassified
“…Простая функционализация О-атома несимметричного лиганда на основе нафтиридинона (12) реакцией с хлор-бис(трет-бутил)фосфином приводит к новому лиганду (13), в котором создаются два четко определенных координационных сайта: участок жесткого донора, содержащий пиколиламиновое плечо, и участок мягкого донора, содержащий фосфинитовое плечо: Авторами отмечено специфическое связывание центра Pt(II) только с участком мягкого фосфинита, что приводит к образованию комплекса (14). Центр Pt(IV) специфически связывается с твердым N-донорным участком (15). Интересно, что при взаимодействии комплекса 14 с йодистым метилом наблюдается немедленная миграция Pt-центра из мягкого в твердый участок, что представляет собой альтернативный путь для образования комплекса 15: Ароматические металлолдианионы являются важными металлоароматическими соединениями из-за их различной реакционной способности и широкого применения в синтетических целях.…”
unclassified
“…Obviously, the [Pt II (L 0.5À ) 2 ] + formulation with L delocalized spin is more appropriate than an alternative [Pt III (L À ) 2 ] + . Mononuclear platinum(III) species are rare [18,19] and should display extremely wide g anisotropy due to the high spin-orbit coupling constant of that heavy metal ion. [18][19][20] The second oxidation separated by 0.36 V from the first is then attributed to formation of a diradical complex [(L )Pt II (L )] 2 + which, however, proved to be too labile for further study.…”
Section: Cyclic Voltammetry Epr and Uv-vis-nir Spectroelectrochemistrymentioning
confidence: 99%